East China Sea Dispute: Paving Japan’s Way to be a Stronger Nations - Shinta Puspitasari (Department of International Relations, Universitas Andalas)
Dispute over East China Sea between two big countries in East Asia, namely China and Japan is not something new. This dispute existed since 1968 which based on historical and territorial issue. However, China and Japan dispute over this area is never been dangerous as it is now: they both use military. Both of them have tried to make an agreement over this issue; yet, it never succeeded. Thus, Japanese policymakers now think about their border. As a result, they change their defence policy to be more aggressive. This is to say, there is a change in Japan’s Self-Defence Force as well as Japan’s security policy. This move may seem as abandonement of Article 9 Showa Constitution that prohibit them to have military, and has been Japanese base in their defence policy. However, Japan Prime Minister think that this bold move is needed in addition to their stronger relationship with the US. Keywords: Japan, China, East China Sea dispute, defence policy